Recent Advances in Pathology: the 2020 Annual Review Issue of The Journal of Pathology - Herrington, C Simon; Poulsom, Richard; Coates, Philip J (The Journal of pathology, 2020)
This year's Annual Review Issue of The Journal of Pathology contains 18 invited reviews on current research areas in pathology. The subject areas reflect the broad range of topics covered by the journal and this year encompass the development and application of software in digital histopathology, implementation of biomarkers in pathology practice; genetics and epigenetics, and stromal influences in disease. The reviews are authored by experts in their field and provide comprehensive updates in the chosen areas, in which there has been considerable recent progress in our understanding of disease. © 2020 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.